3D printed ultra-fast photothermal responsive shape memory hydrogel for microrobots. (3rd December 2021) - Zhan, Ziheng; Chen, Lei; Duan, Huigao; Chen, Yiqin; He, Min; Wang, Zhaolong
Abstract: Hydrogels with stimuli-responsive capabilities are gaining more and more attention nowadays with prospective applications in biomedical engineering, bioelectronics, microrobot, etc. We develop a photothermal responsive hydrogel based on N-isopropylacrylamide that achieved a fast and reversible deformation manipulated only by near-infrared (NIR) light. The hydrogel was fabricated by the projection micro stereolithography based 3D printing technique, which can rapidly prototype complex 3D structures. Furthermore, with the variation of the grayscale while manufacturing the hydrogel, the deformation of the hydrogel structure can be freely tuned within a few seconds by losing and absorbing water through adjusting the intensity and the irradiation direction of the NIR light, showing a potential application in ultra-fast object grabbing and transportation. The present study provides a new method for designing ultrafast photothermal responsive hydrogel based microrobot working in water.